2009
DOI: 10.3113/fai.2009.0613
|View full text |Cite
|
Sign up to set email alerts
|

Hindfoot Motion following Reconstruction for Posterior Tibial Tendon Dysfunction

Abstract: In this preliminary postoperative study, surgical reconstruction for PTTD effects quantifiable objective improvement in walking velocity, hindfoot motion and power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The novel assessment from our study was the bony kinematics of cadaveric specimens with simulated Stage II PTTD before and after simulated FDLTT. Numerous studies looked at in vivo hindfoot kinematics in patients with PTTD, and in general, small but significant changes in the hindfoot complex kinematics were observed. Niki et al tested cadaveric Stage II PTTD feet with and without the functionality of the PTT, and found that the PTT had little effect in overcoming the ligamentous laxity of the flatfoot model.…”
Section: Discussionmentioning
confidence: 99%
“…The novel assessment from our study was the bony kinematics of cadaveric specimens with simulated Stage II PTTD before and after simulated FDLTT. Numerous studies looked at in vivo hindfoot kinematics in patients with PTTD, and in general, small but significant changes in the hindfoot complex kinematics were observed. Niki et al tested cadaveric Stage II PTTD feet with and without the functionality of the PTT, and found that the PTT had little effect in overcoming the ligamentous laxity of the flatfoot model.…”
Section: Discussionmentioning
confidence: 99%
“…The Milwaukee Foot Model from previous studies was used. 7,13,14,33,44,45 This is a 4-segment model that allows evaluation of the tibia, hindfoot, forefoot, and hallux (Figure 1). The focus of study was the motion of the ankle and of the hindfoot, based on our hypothesis.…”
Section: Gait Analysismentioning
confidence: 99%
“…Of the clinical populations tested the most common were rheumatoid arthritis (Turner et al, 2006;Khazzam et al, 2007;Turner and Woodburn, 2008), and posterior tibial tendon dysfunction (Ness et al,. 2008;Brodsky et al,. 2009;Houck et al,.…”
Section: Secondary Analysis Of Clinical Utilitymentioning
confidence: 95%